Between international financial reporting standards (IFRSS) and financial accounting standards (FASS): the debate continues - Mohd Hussan, Subithabhanu; Sulaiman, Maliah (International Islamic University Malaysia, 2016)
This article continues the on-going debate on what would be the more relevant accounting standards for Islamic banks. It addresses this important issue by first examining the differences between IFRSs and FASs in light of their objectives, scope, and suitability for adoption by Islamic banks in reporting their sharī‘ah-compliant transactions. Specifically, the study approaches the issue from the ethics of reporting, that is on the possibility of misreporting leading to sharī‘ah non-compliance. Most importantly, in reviewing selected standards of IFRSs and FASs, the study finds that the over-emphasis on ‘comparability’ may potentially lead to misreporting. Thus, it views sharī‘ah a compliance from a broader perspective instead of only limiting it to the execution of underlying transactions. Finally, it calls for collaboration between the International Accounting Standards Board (IASB) and the Accounting and Auditing Organization of Islamic Financial Institutions (AAOIFI).